Acinar cell carcinoma: a report of 19 cases with a brief review of the literature. Issue 1 (December 2016) - Wang, Yu; Wang, Sinan; Zhou, Xuan; Zhou, Hongyuan; Cui, Yunlong; Li, Qiang; Zhang, Lun
Abstract Background Acinar cell carcinoma (ACC) is a relatively rare pancreatic neoplasm with poorly defined prognosis. This study aimed to investigate this rare pancreatic neoplasm through comparing patients with ACC to pancreatic ductal cell adenocarcinoma (DCA). Methods Tianjin Medical University Cancer Institute and Hospital pathology database was reviewed from 1995 to 2015, and 19 patients with pathologically confirmed ACC were enrolled while 19 conventional DCA patients assigned randomly as control. Retrospective review and follow-up were performed for each patient. Regression methods were used to identify differences between ACC and DCA. Results In our study, most patients suffered from abdominal or back pain, and no lipase hypersecretion syndrome was observed. For ACC, resected cases had better survival than those without resection, and earlier staging was related to longer survival. Resection with postoperative adjuvant therapy had a better outcome than surgery alone. Twelve cases developed recurrence. Compared to DCA, ACC had earlier staging and better survival. The overall 1-, 2-, and 5-year survival rates for patients with ACC were 73.7, 26.3, and 5 %, respectively. Conclusions ACC carries a better prognosis than DCA and a similarly high recurrence rate, while surgical resection proved the best first-line approach for it. A well-planned neoadjuvant or adjuvant chemoradiotherapy indeed benefit the patients with ACC.